Religious Practice and Pro-Environmental Behavior Among Generation Z: A Correlational Study of Islamic Ritual Worship in DKI Jakarta - Suhardin Suhardin; Erwina Erwina (Glosains: Jurnal Sains Global Indonesia, 2026)
requiring active participation from all groups, including Generation Z as future agents of change. In addition to external factors, individual values such as religious practices may influence pro-environmental behavior. However, studies examining the relationship between religious worship — particularly salat (prayer) and sawm (fasting) — and pro-environmental behavior among Generation Z remain limited. Objective: This study aims to describe the pro-environmental behavior of Generation Z and their practice of salat and sawm, as well as to analyze the relationship between these religious practices and pro-environmental behavior. Method: This research used a correlational approach involving 94 Generation Z students from junior high and senior high schools in DKI Jakarta. The sample was selected using purposive random sampling. Data were analyzed to identify the relationship between salat and sawm practices and pro-environmental behavior. Results: The findings show that Generation Z demonstrates a high level of pro-environmental behavior, as well as high levels of salat and sawm practices. The correlation test results indicate a significant relationship between salat and sawmand pro-environmental behavior. Conclusion: This study concludes that religious practices, particularly salat and sawm, are positively associated with pro-environmental behavior among Generation Z. Therefore, strengthening religious values may contribute to enhancing pro-environmental behavior, as higher levels of worship are associated with higher levels of pro-environmental behavior.